Improved outcome and cost effectiveness in ablation of persistent atrial fibrillation under general anaesthetic. Issue 6 (21st April 2017) - Martin, Claire A; Curtain, James P; Gajendragadkar, Parag R; Begley, David A; Fynn, Simon P; Grace, Andrew A; Heck, Patrick M; Salaunkey, Kiran; Virdee, Munmohan S; Agarwal, Sharad
Abstract: Aims: Outcome of persistent atrial fibrillation (AF) ablation remains suboptimal. Techniques employed to reduce arrhythmia recurrence rate are more likely to be embraced if cost-effectiveness can be demonstrated. A single-centre observational study assessed whether use of general anaesthesia (GA) in persistent AF ablation improved outcome and was cost-effective. Methods and results: Two hundred and ninety two patients undergoing first ablation procedures for persistent AF under conscious sedation or GA were followed. End points were freedom from listing for repeat ablation at 18 months and freedom from recurrence of atrial arrhythmia at 1 year. Freedom from atrial arrhythmia was higher in patients who underwent ablation under GA rather than sedation (63.9% vs. 42.3%, hazard ratio (HR) 1.87, 95% confidence interval (CI): 1.23–2.86, P = 0.002). Significantly fewer GA patients were listed for repeat procedures (29.2% vs. 42.7%, HR 1.62, 95% CI: 1.01–2.60, P = 0.044). Despite GA procedures costing slightly more, a saving of £177 can be made per patient in our centre for a maximum of two procedures if all persistent AF ablations are performed under GA. Conclusions: In patients with persistent AF, it is both clinical and economically more effective to perform ablation under GA rather than sedation.